Pengaruh Model Problem Based Learning (PBL) Terhadap Motivasi Belajar Siswa Pada Pelajaran PAI Kelas VII Sekolah Menengah Pertama Negeri 1 Mapat Tunggul - Kusumaputra, Adi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the quality of learning through the application of active learning methods. The research was conducted in two cycles, each with a different approach. Cycle I used conventional methods, which were found to be less effective in increasing student engagement. In Cycle II, active learning methods were implemented by involving students in discussions, experiments, and various activities that encouraged active participation. The results of the study show a significant improvement in student motivation and understanding. Based on these findings, it can be concluded that active learning, which involves students directly, can enhance learning outcomes and create more enjoyable and meaningful learning experiences.